PENGGUNAAN METODE PEMBELAJARAN PADA PELATIHAN TATA RIAS KELOMPOK PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI NAGARI GANGGO HILIA KABUPATEN PASAMAN - Mimi Susanti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2015)
This research is based on the success of the learners cosmetology training on empowerment group and family welfare in Nagari Ganggo Hilia, Pasaman, it seens that more than half of learners have work. Researcher suspect the cause of success learning because learning method used by instructor. This research aims to describe the use of lecture method, demonstration method and drill method. The kind of this research is quantitative descriptive with population learners cosmetology training totaling 16 people, as respondents. Technique of data collection was a questionnaire. Data collected tool was a quetionaire sheet (quetioner), and analyzed with a percentage formula. The result showed that the instructor used the lecture method very good, instructor used demonstration method very good, and instructor used method drill good